ASSESSING MICRO AND SMALL BUSINESS’ ENERGY MANAGEMENT TO OPTIMIZE MICRO AND SMALL BUSINESS’ PRODUCTION: CASE STUDY - Mawati, Maria K.; Kindangen, Paulus .; Tasik, Hizkia . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Energy is used in the production process as the inputs. Micro and small business have big role in the economic growths. This micro and small business? use the energy as an input. This study aims to describe the current energy management. The informants are the owner of micro and small business and the household. Using a qualitative method with case study approach this study found that energy that act as input in the production process could affect the production input. The energy needs are different for each micro and small business. Cheaper energy could reduce the energy spending for the micro and small business home activity, but not for their production activity. Energy spending of the micro and small business does have significance effect to the micro and small business production output. Cheaper energy does reduce the energy cost in number but it does not increase the production output in long-term. They are currently not saving the energy and only a few have intention to save in future. Micro and small business need to use renewable energy in their home activities, the cost could be considered high, but in long term it is cheaper and more environmental friendly.Keywords: energy availability, energy management, micro and small business, bitung